2021
DOI: 10.1017/s002531542100045x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of mangrove forest and association with strandings of Antillean manatee (Trichechus manatus) calves in Paraíba, Brazil

Abstract: Estuaries in Brazil are highly threatened environments and habitat loss is the main influential factor for the increase in the number of strandings of Antillean manatee (Trichechus manatus) calves in the north-eastern region of the country. The aim of the present study was to analyse and quantify the spatiotemporal dynamics of mangroves in the state of Paraíba and the association with manatee calf stranding events. The study area encompassed 10 remaining mangroves along the coast of the state, four of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…In the present study, the positive and significant correlation between pressure and threat showed that the impacts on the marine manatee and the ecosystem services are expected to continue in the future. The results of this work corroborated with the pressure and threat categories presented by other authors, such as hunting (Luna et al 2008a(Luna et al , 2008b; accidental capture in fishing nets (Lima et al 2007;ICMBio 2011); alteration and destruction of breeding habitats (ICMBio 2011; Medeiros et al 2021), which intensifies the stranding of calves (Parente et al 2004;Medeiros et al 2021); siltation of estuaries (Anzolin et al 2012); the presence of contaminants in the environment (Anzolin et al 2012); ingestion of garbage; noise pollution; climate change (ICMBio 2011) and collisions with motorized vessels (Borges et al 2007). In our study, calf stranding, the silting of estuaries and habitat destruction were among the most cited pressures and threats.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the positive and significant correlation between pressure and threat showed that the impacts on the marine manatee and the ecosystem services are expected to continue in the future. The results of this work corroborated with the pressure and threat categories presented by other authors, such as hunting (Luna et al 2008a(Luna et al , 2008b; accidental capture in fishing nets (Lima et al 2007;ICMBio 2011); alteration and destruction of breeding habitats (ICMBio 2011; Medeiros et al 2021), which intensifies the stranding of calves (Parente et al 2004;Medeiros et al 2021); siltation of estuaries (Anzolin et al 2012); the presence of contaminants in the environment (Anzolin et al 2012); ingestion of garbage; noise pollution; climate change (ICMBio 2011) and collisions with motorized vessels (Borges et al 2007). In our study, calf stranding, the silting of estuaries and habitat destruction were among the most cited pressures and threats.…”
Section: Discussionsupporting
confidence: 90%
“…Manatees prefer naturally sheltered areas such as coves, bays and estuaries and are sensitive to disturbance caused by the construction and operation of cities, ports, marinas, shipyards, salt works, shrimp farms and other anthropogenic structures and activities in these areas (Aquasis, 2016). Such habitat modifications are associated with an increase of manatee calf stranding events along the north-eastern Brazilian coast (Parente et al, 2004; Meirelles, 2008; Medeiros et al, 2021). Without access to undisturbed estuaries, females give birth in open water, where newborns may become separated from mothers and stranded on the coast (de Lima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…O potencial de impacto da carcinicultura aos peixes-bois não se limita apenas aos contaminantes provenientes da criação e processamento dos camarões, mas também tem um papel determinante no encalhe dos filhotes, principalmente nos estados do Ceará e do Rio Grande do Norte, devido aos danos causados por esta atividade às áreas de águas calmas encontradas na foz dos rios, normalmente utilizadas pelas fêmeas de peixes-bois ao parir (Meirelles, 2008;de Almeida, 2010;Balensiefer et al, 2017). O recente estudo de Medeiros et al (2021) avaliou a relação da integridade das florestas de manguezais no estado da Paraíba com encalhes de peixes-boi nos últimos 39 anos, evidenciando que o menor número de encalhes de filhotes de peixes-bois-marinhos registrado no estado ocorreu em períodos em que os ambientes manguezais estavam menos degradados.…”
Section: Carciniculturaunclassified